Activation or suppression of NFκB by HPK1 determines sensitivity to activation-induced cell death - Brenner, Dirk; Golks, Alexander; Krammer, Peter H.; Arnold, Rüdiger (The EMBO journal, 2005)
Restimulation of the T-cell receptor (TCR) in activated T cells induces CD95 (Fas/Apo-1)-mediated activation-induced cell death (AICD). The TCR-proximal mechanisms leading to AICD are elusive. Here we characterize hematopoietic progenitor kinase 1 (HPK1) as a differentially regulated TCR-proximal signaling protein involved in AICD of primary T cells. We show that HPK1 is a functional component of the endogenous I?B kinase (IKK) complex and is crucial for TCR-mediated NF?B activation. While full-length HPK1 enhances IKK? phosphorylation, siRNA-mediated knockdown of HPK1 blunts TCR-mediated NF?B activation and increases cell death. We also demonstrate proteolytic processing of HPK1 into HPK1-C, specifically in AICD-sensitive primary T cells. The cleavage product HPK1-C sequesters the inactive IKK complex and suppresses NF?B upon TCR restimulation by binding to IKKα and IKK?. T cells of HPK1-C transgenic mice are sensitized towards TCR-mediated AICD. Consequently, preventing HPK1-C generation in primary T cells by siRNA-mediated knockdown results in decreased AICD. Thus, these results show a novel mechanism of sensitization of T lymphocytes towards AICD by suppression of NF?B, and propose that HPK1 is a life/death switch in T lymphocytes.
Gesehen am 04.03.2021